Intersectionality of disability and cultural/linguistic diversity in the UK: a literature review - Kaplan, Gamze; Celik, Pinar (Frontiers in Education, 2023)
This article explores the intersectionality of cultural and linguistic diversity and having a child with a disability, highlighting the unique challenges faced by parents from a minority ethnic background at this intersection. With increasing globalization, diverse and multicultural populations have become more prevalent, necessitating inclusive systems that address the unique needs of minority ethnic groups. Understanding the experiences of parents at the intersection of cultural and linguistic diversity and having a child with a disability is crucial for providing equitable access to education and support. This paper provides an overview of studies conducted in the UK, focusing on the challenges faced by culturally and linguistically diverse families from a minority ethnic background with children with disabilities and emphasizing factors such as religion, cultural beliefs, language barriers, and unique insights into specific populations. The findings emphasize the need for a comprehensive understanding of the intersectionality of cultural and linguistic diversity and disability to create inclusive educational environments that empower all children, irrespective of their cultural background or abilities.